2022
DOI: 10.3389/fenvs.2022.902457
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Role of Risk Perception and Environmental Quality on the Relationship Between Risk Knowledge and Traveler’s Intention in COVID-19

Abstract: The recent outbreak of epidemic disease (COVID-19) has dramatically changed the socio-economic and environmental dynamics of the world. In particular, it affects human movement, travel intentions, and ambient air pollution amid rising stringency measures. Therefore, this study examines the influence of tourism knowledge, environmental vulnerability, and risk knowledge on travelers’ intentions in China’s tourism industry during COVID-19. To address the study objectives, an online survey questionnaire was create… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…There were regional differences in risk perception. Another study examined the relation between risk perception and tourist's intention to visit a place (Yang et al 2022). It was found that risk perception and attitude towards risk had a mediating effect between knowledge and travel intention.…”
Section: Health Risk Perception Based Studiesmentioning
confidence: 99%
“…There were regional differences in risk perception. Another study examined the relation between risk perception and tourist's intention to visit a place (Yang et al 2022). It was found that risk perception and attitude towards risk had a mediating effect between knowledge and travel intention.…”
Section: Health Risk Perception Based Studiesmentioning
confidence: 99%
“…Behavioural economics theory suggests that psychological factors should be introduced to analyse human decisionmaking behaviour effectively 6 . Risk is ubiquitous and can be divided into many categories of risk according to different classifications, such as natural risk and social risk according to the source, life risk, ecological risk and economic risk according to the consequences 7 . Liu Li et al found that risk perception positively affects farmers' adoption of soil and water conservation farming techniques 8 .…”
Section: Impact Of Risk Perception On Herders' Pro-environmental Beha...mentioning
confidence: 99%